2010
DOI: 10.1007/s10461-010-9808-7
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Related Behavioral Studies of Men Who Have Sex with Men in China: A Systematic Review and Recommendations for Future Research

Abstract: HIV prevalence among men who have sex with men (MSM) has increased significantly in China since early 2000, with MSM accounting for 32.5% of the newly infected HIV cases in China in 2009. This study reviews a total of 33 studies published in English literature on MSM in China from 2000 to 2009. Existing studies indicated that frequently MSM in China were married (especially older MSM); a majority were migrants and self-identified as gay. A large and increasing proportion of MSM sought sexual partners online. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 42 publications
5
63
2
Order By: Relevance
“…Consistent with trends in sexarche in the general population and MSM in developed countries [9, 10, 14], we found that younger age was associated with earlier anal sexarche, which could be explained by the changing social and cultural norms toward sex in general [15, 16], and easier access for Asian MSM to meet sex partners at younger age (e.g., Internet and emerging gay venues) [17, 18]. Although younger Asian MSM tended to have sexarche at an earlier age, we also found that they were less likely to have unprotected sex during their anal sexarche compared to older participants.…”
Section: Discussionsupporting
confidence: 73%
“…Consistent with trends in sexarche in the general population and MSM in developed countries [9, 10, 14], we found that younger age was associated with earlier anal sexarche, which could be explained by the changing social and cultural norms toward sex in general [15, 16], and easier access for Asian MSM to meet sex partners at younger age (e.g., Internet and emerging gay venues) [17, 18]. Although younger Asian MSM tended to have sexarche at an earlier age, we also found that they were less likely to have unprotected sex during their anal sexarche compared to older participants.…”
Section: Discussionsupporting
confidence: 73%
“…Thus, the development of effective interventions in China is essential. China's HIV epidemic is increasingly transmitted through sex and will grow from the current 740,000 cases [1,2] to an estimated 1.2 million cases by 2015 [3], while the annual HIV infection rate has been rising steadily since the 1990s: increases of 30% between 1995 and 2000, 58% during 2001, 122% during 2003, and 45% during 2007 [4,5]. As in many other Asian countries, men who have sex with men (MSM) represent an increasing proportion of new infections in China: 0.2% in 2001, 7.3% in 2005, 12.2% in 2007, and 32.5% in 2009 [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Other regional and sentinel surveys reveal high HIV prevalence rates among MSM in many large metropolitan areas: 5.2% in Beijing in 2006 [11], 7-8% in Chongqing [12,13], and 10.6% in Chengdu [14], while rising HIV prevalence rates among MSM were also reported in Nanjing [15], Shenyang [16], Shenzhen [17,18], Jinan [19], and Jiangsu Province [20]. The increased number of reported cases among MSM may result from a combination of factors, including a higher disclosure rate that can be attributed to increasing cultural acceptance of homosexuality and the expanding size of sexual networks [4,21] and increased presence of risk behaviors [2,16,[22][23][24][25][26] with persistently high rates of unprotected anal intercourse (UAI) among MSM [10,14,27] in China. It is undeniable that China, like other Asian countries, is facing an expanding HIV epidemic among its 10 to 20 million MSM [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research suggests that unprotected anal intercourse (UAI) is a major risk factor for HIV infection among MSM and that the prevalence of UAI among MSM is high in China (e.g., the estimated prevalence of UAI was 50% in 2008-2012) 6,7,8,9 . Further studies are needed to explore the factors associated with UAI, and other sexual risk behaviours, among MSM in China, in order to better target behavioral prevention strategies.…”
Section: Introductionmentioning
confidence: 99%